Sustainable Livelihood Approach for Industrial Communities in Bergas Kidul Village in Mitigating Climate Change and Reducing the Effect of Greenhouse Gases - Fitriyani, Nurul Ardian; Sari, Monika Anggun Jatmika; Sarasati, Christina Dewi (Prospect: Jurnal Pemberdayaan Masyarakat, 2024)
Global warming is a global phenomenon triggered by human activities, especially those related to fossil materials and land use change activities. As a company that cares about preserving natural resources as well as social and environmental responsibility, PT Industri Jamu Dan Farmasi Sido Muncul. Tbk (Sido Muncul) created a community development program in Bergas Kidul Village in Bergas District, Semarang Regency. As a village located in an industrial area, it is very vulnerable to land use change and large unemployment due to uncertainty in livelihoods. This research uses a sustainable livelihood approach which describes vulnerabilities and potential according to the study results. Calculations of social, economic and environmental impacts are obtained from analysis of field data combined with secondary data. The calculation of greenhouse gas emissions from the cattle communal program uses the IPCC Tier 1 method, while for CO2 absorption by plants uses the plant's CO2 absorption capacity value. The environmental impact resulting from the program is one of the efforts to mitigate climate change by reducing greenhouse gas emissions released into the atmosphere through planting trees amounting to 21,600 kg CO2/year and processing livestock manure into fertilizer amounting to 1,018.64 kg CO2e/year.